EFFECTS OF INTERPROFESSIONAL COLLABORATION PROGRAM IN COMMUNITY ON THE PERCEPTION OF PHARMACY AND MEDICAL STUDENTS - Christianus Heru Setiawan; Rita Suhadi; Phebe Hendra; Fenty Fenty; Dita Maria Virginia; Gregorius Bhaskara Wikanendra (Sanata Dharma University, 2020)
Cardiovascular disease is the highest cause of mortality in Indonesia. One of the factors that causes the disease is low level of health awareness, including healthy lifestyle and health control. Improving public health awareness can be done by providing health education in collaboration with interprofessional health services. A collaboration involving students from various health-related disciplines aims to build good collaboration in the future after the corresponding students become health workers. This study is quasi-experimental. Students from health-related disciplines, especially pharmacy and medical students, were authorized to work directly in health screening and to provide education to the community. Students perceptions on the Interprofessional Collaboration (IPC) program were explored through Student Perceptions of Physician-Pharmacist Interprofessional Clinical Education (SPICE) questionnaire, which were given before and after the community project. Among 87 SPICE questionnaires, 78 questionnaires filled in completely were collected from pharmacy and medical students. The results of the questionnaire showed good perceptions before and after activities in the community with mean scores of 4.46 (0.35) and 4.5 (0.37) respectively. Wilcoxon test results found no significant difference on the total SPICE scores before and after the activity (P .05). One item from the SPICE questionnaire, which was the seventh item related to understanding the role of other professionals in the interdisciplinary team, had a significant increase (P .05).